Propuesta de automatización de las compuertas del canal de riego del ramal de la parroquia limones del cantón Zapotillo. - Rivera Vidal, Edison Javier (2016)
To fullfill goals on present research work methodology proposed consisted on: review on technical literature about irrigation channel, control elements and automation instruments. In addition A description on operation and functioning of irrigation channel called “Limones” located in Zapotillo a district in Loja – Ecuador was done. Also, a verification on existent number of gates in the system was performed. In addition, a redesign for opening and closing gates was performed based on calculation of the power on reduction motor, besides the analysis of the mechanical elements implied on operation. The selection on the equipment required on automation process, such as: water level metering sensors, positioning sensors for gates was done. The system uses a PLC S7 1200 on Siemens Sismatic brand which sequencially turned on and off the system. The programming of the PLC used TIA Portal v13, besides a SCADA system supported in Vijeo Citec software used for monitoring, supervising and controlling the system process from the Control Station. The power supply on each one of the remote stations used solar panels. For simulating radiolinks wireless communication between stations the software Radio Mobile v.10 was used. There is a budget proposed for project investment and an economic analysis that will let to determine viability on this project. Finally, conclusions are drawn focused on each specific objective proposed and recommendations to take into account